Correlation of Gratitude and Patience to Subjective Well-Being on Honorary Teachers - Majdi, M. Zuhdi Zainul Majdi; Hendar, Kus; Sa’adah, Sa’adah (Indonesian Institute for Counseling, Education, and Therapy & Indonesian Counselor Association, 2024)
Humans strive to create a prosperous life, both physical, social and psychological conditions, so that the quality of life improves, including honorary teachers. Psychological well-being has a relationship with the behavior of gratitude and patience. The research aims to determine the correlation of gratitude and patience with subjective well-being in honorary teachers. This research uses quantitative with explanatory correlational type. Subjects were taken using purposive sampling. Respondents in this study were 155 people. Data collection used 3 instruments; gratitude scale, patience scale, and subjective well-being scale. Data analysis used multiple linear regression with the help of SPSS. The results of this research show that there is a significant correlation between gratitude and patience on subjective well-being in honorary teachers. The higher the level of gratitude and patience, the higher the subjective well-being experienced by honorary teachers.